The Effectiveness of a Pain Management Program on Intensify of Pain and Quality of Life Among Cancer Patients in Myanmar - Hein Thu; Tintin Sukartini (Universitas Airlangga, 2017)
Introduction: Cancer is one of the leading causes of death worldwide and is rapidly becoming a global pandemic. Cancer pain significantly affects the diagnosis, quality of life and survival of patients with cancer. The aim of this study is to analyse the effect of a Pain Management Program (PMP) on pain and quality of life in a patient with cancer.Methods: This study used a quasi-experimental design with a randomised pre-post test design approach. The data was collected from cancer patients in No 2 Military Hospital (500-Bedded), Yangon, Myanmar. The patients were recruited using a random allocation sampling technique and consisted of 30 respondents (experimental group) and 30 respondents (control group) taken according to the inclusion criteria. The Short Form-McGill Pain Questionnaire 2 (SF-MPQ 2) was used to assess pain, and The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30) was used to assess the quality of life.Results: A MANOVA test was used to analyse the effect of PMP. It showed that 1) PMP decreased the pain and 2) PMP increased the quality of life in patients with cancer.Conclusion: Improvements in the quality of life and to do with pain-related cancer suggests that the vicious cycle of chronic pain may be alleviated by PMP. As we look at the results, PMP can be an effective treatment to be used by nurses for decreasing pain and increasing the quality of life in patients with cancer.